LEBIH MEMBERDAYAKAN ARBITRASE UNTUK PENYELESAIAN SENGKETA BISNIS - Wika Yudha Shanty (University of Merdeka Malang, 2013)
On normative perspective, court upheld law based on the regulation and justice. Judicature was carried outfast, simple and cheap. However, in practice, judicature process always spent much time because of the formalprocedure. From entering the case to court until decision or finding of court which got the law confirmation, italways needed much time, complicated process, and much money. Especially for businessmen, case or longconflict would inflict financial loss. In business world, special skill was needed to decide special conflict inbusiness world which was not always known by every judge, for example contract. To be able to investigate anddecide those kinds of conflicts completely, it was not enough only having knowledge about regulation as thelaw principle. To make a business conflict completion reflected justice or it could be accepted by all parties, lawsystem gave alternative of conflict completion out of court. By this way, the burden of court was decreased andmore than that the completion which was the will meeting would not cause a new case. The character ofcompletion above became an alternative which had to be passed by all parties in conflict, especially businessconflict, to get the effective solution and to decrease or even to abolish conflict because of business.